Mentorship, Good Governance and Development in Nigerian Organizations: A Comparative Analysis - Daddie, Joel Augustus -; Adamu, Isah (NIU Journal of Social Sciences, 2023)
This paper examines mentorship, Good Governance and Development in Nigerian organizations: A comparative analysis. The paper considers major issues/challenges affecting mentorship, Good Governance and Development in Nigeria Such as unwillingness of modern day Mentors to effectively Coach Mentees for fear of those mentees becoming a threat to them in the near future; Absence of good mentors or scarcity of same as well as the lack of humble and teachable mentees in our society. Mentorship methods were addressed and linked to training which eventually also leads to good governance and development. The paper argues that if good governance must be bequeathed to future generations, then the present generation of leaders must be willing to exercise good mentorship in all ramifications, even in the academia. It was suggested amongst others, that mentorship should be taken seriously especially by lecturers, politicians, and officers in government, to ensure National Development. Keywords: Mentorship, Good Governance, Development, Mentor, Mentee.